The Influence of Lysed Biomass of Wine Yeast on the Preservation of Aromatic Substances of Grapes during Alcoholic Fermentation - M. , Khositashvili; M. , Ormotsadze; A. , Kiknadze; L. , Kotorashvili; T. , Khositashvili; M. , Mikiashvili; N. , Khomasuridze (American Journal of Biology and Natural Sciences, 2025)
This study investigates the effect of lysed wine yeast biomass on the preservation of grape aromatic compounds during alcoholic fermentation. The aim was to assess how the addition of enzymatically lysed yeast biomass influences the physiological activity of pure yeast cultures. The research was conducted using Rkatsiteli grape must, lysed yeast biomass, and the resulting wine material. Gas chromatography analysis demonstrated that fermentation in experimental wines was more complete compared to control samples.